2017
DOI: 10.1590/1980-4415v31n59a04
|View full text |Cite
|
Sign up to set email alerts
|

Formulação de Problemas Matemáticos de Estrutura Multiplicativa por Professores do Ensino Fundamental

Abstract: ResumoO presente estudo investiga como professores do Ensino Fundamental concebem e formulam situações-problema inseridas no campo conceitual das estruturas multiplicativas. Trinta e nove professores do 1º ao 9º ano de escolas públicas foram solicitados a formular problemas matemáticos que pudessem ser resolvidos por meio de multiplicação e/ou de divisão. Os resultados mostram que os professores investigados compreendem o que uma situação multiplicativa significa e formulam problemas apropriadamente, sendo pou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
3
6
0
8
Order By: Relevance
“…Faced with this scenario and considering the relevance of this topic for mathematics education, this research aims to examine the characteristics of mathematical problems posed by elementary school teachers, analysing aspects related to the verbal statement and the types of problems they formulate. The investigation continues and deepens the results obtained in a previous investigation with multiplication and division problems (Spinillo et al, 2017), as well as expands the analyses carried out by including addition and subtraction problems. This study seeks to examine whether the characteristics of the problems posed varied if the teacher taught in early school grades in which the emphasis is on the teaching of additive, or in more advanced school grades in which the emphasis is on the teaching of multiplicative concepts.…”
Section: Research On Teachers' Mathematical Knowledge and The Charactsupporting
confidence: 63%
See 3 more Smart Citations
“…Faced with this scenario and considering the relevance of this topic for mathematics education, this research aims to examine the characteristics of mathematical problems posed by elementary school teachers, analysing aspects related to the verbal statement and the types of problems they formulate. The investigation continues and deepens the results obtained in a previous investigation with multiplication and division problems (Spinillo et al, 2017), as well as expands the analyses carried out by including addition and subtraction problems. This study seeks to examine whether the characteristics of the problems posed varied if the teacher taught in early school grades in which the emphasis is on the teaching of additive, or in more advanced school grades in which the emphasis is on the teaching of multiplicative concepts.…”
Section: Research On Teachers' Mathematical Knowledge and The Charactsupporting
confidence: 63%
“…As Souza and Magina (2017), Spinillo et al (2017) investigated how teachers from the 1 st to the 9 th grades of elementary school posed multiplication and division problems. The results showed that despite formulating the problems appropriately, teachers had a limited view of this activity.…”
Section: Research On Teachers' Mathematical Knowledge and The Charactmentioning
confidence: 99%
See 2 more Smart Citations
“…Autores como Nogueira (2001), Pais (2001Pais ( , 2006, Pavanello (2004) e Santos (2008) apresentam críticas quanto ao papel transmissivo da escola privilegiando em demasia os conteúdos conceituais e apontam a necessidade de rever a formação inicial dos professores. Spinillo et al (2017) concluíram que professores do 1º ao 9º ano do Ensino Fundamental têm dificuldades em formular problemas que envolvam diferentes relações no âmbito das estruturas multiplicativas, sendo necessário desenvolver com o professor do Ensino Fundamental a habilidade de formular problemas. Resultados similares foram verificados por Cunha (2015) em pesquisa com professores do Ensino Médio.…”
Section: Introductionunclassified